Thermal mechanical modeling and residual stress prediction for laser direct energy deposition of 30CrNi2MoVA steel considering solid-state phase transformation - Peng Rong; Qingsong Bai; Ming Yin; Wei Li; Yanxuan Song; Fenglei Zheng (Journal of Materials Research and Technology, 2024)
Laser directed energy deposition (LDED), a highly promising metal additive manufacturing (AM) technology, has garnered widespread attention across various industries. However, local high-energy input during AM can generate residual stress (RS), which may cause deformation and even cracking of the parts. Due to the evolution of RS is influenced by temperature gradients, cooling rates and solid-state phase transformation(SSPT), accurately predicting RS remains challenging. To tackle this issue, a thermal-metallurgical-mechanical coupled model of 30CrNi2MoVA steel in LDED is established. To account for the influence of SSPT on the evolution of RS, the phase transformation kinetics model for 30CrNi2MoVA steel is developed based on thermal expansion experiments and integrated into mechanical computations. Using this model, the thermal cycle history, microstructure distribution and RS level of LDED fabricated parts are discussed in detail, and the accuracy of the model is verified through characterization experiments such as thermocouples, scanning electron microscopy and X-ray diffraction. The simulation results show that the RS of thin-walled parts is related to the scanning direction, and the maximum principal stress along the scanning direction is the highest. The microstructure of thin-walled parts is mainly composed of martensite with a small amount of bainite. Compared to models that do not consider SSPT effects, the overall stress magnitude of models that consider SSPT significantly decreases, and the surface RS state transitions from tensile stress to compressive stress. The proposed thermal-metallurgical-mechanical coupled model has the potential to accurately predict and understand the stress behavior and performance changes of 30CrNi2MoVA steel in LDED.